Exploring ultrasound-induced free radical formation: A comparative study in water and sour cherry juice using glutathione and terephthalic acid indicators - Nursena Aktı; Semanur Yildiz (Ultrasonics Sonochemistry)
This study aims to assess free radical (FR) generation potential of ultrasound in water and sour cherry juice (SCJ) model systems using an indirect method with specific indicators including glutathione (GSH), a well-known antioxidant, and terephthalic acid (TPA), which fluoresces upon oxidation. Initially, aqueous GSH solutions were subjected to ultrasound at varying amplitudes (60 % and 80 %) for up to 30 min using probes of different diameters (13 mm and 19 mm) to identify maximal oxidation conditions. FR formation was monitored using UPLC equipped with diode array detector and fluorescence spectrophotometer for GSH and TPA oxidation, respectively. Increasing sonication time decreased GSH and increased oxidized glutathione (GSSG) in water for both probes; however, the 19 mm probe generated five times more GSSG than the 13 mm, implying a substantially higher rate of FR formation. Subsequently, ultrasound was applied to aqueous TPA solution using the 19 mm probe—representing the more challenging conditions—at a previously optimized amplitude (67 %) during 30 min. Time-course water samples showed a steady increase in TPA fluorescence intensity with longer sonication durations, suggesting that oxidation reactions driven by FRs were progressing over time in water. Following sonication of GSH- and TPA-added SCJ under the same conditions, analysis by LC-QTOF-MS and fluorescence spectrophotometry revealed no GSSG or fluorescence formation, confirming the absence of notable oxidation of both indicators, likely due to the juice’s complex composition (e.g., presence of antioxidant compounds). This study offers key insights into how ultrasound conditions affect FR formation in water and SCJ media by stabilizing them in detectable forms.